Re-conceptualising and re-positioning Australian library and information science education for the 21st century : final report 2011. - Partridge, Helen; Hanisch, Jo; Hughes, Hilary; Henninger, Maureen; Carroll, Mary; Combes, Barbara; Genoni, Paul; Reynolds, Sue; Tanner, Kerry; Burford, Sally; Ellis, Leonie; Hider, Philip; et al. (Australian Learning and Teaching Council, 2011)
How can Australian library and information science (LIS) education produce, in a sustainable manner, the diverse supply of graduates with the appropriate attributes to develop and maintain high quality professional practice in the rapidly changing 21st century? This report presents the key findings of a project that has examined this question through research into future directions for LIS education in Australia. The purpose of the project was to establish a consolidated and holistic picture of the Australian LIS profession, and identify how its future education and training can be mediated in a cohesive and sustainable manner. Includes 11 recommendations made by the research team. [Executive summary, ed]